KARAKTERISTIK FISIS ALUMINOSILIKAT GEOPOLIMER BERBASIS SILIKA SEKAM PADI UNTUK APLIKASI FAST IONIC CONDUCTOR - Agus Riyanto; Simon Sembiring; Junaidi Junaidi (Reaktor, 2017)
The study aims to investigate the effect of calcination temperatures on the phase formation and electrical properties of aluminosilicate geopolymer prepared from rice husk silica and sodium aluminate. The samples were calcined at temperature from 150 oC to 550 oC, the development of structures was characterized using x-ray difraction (XRD) and the electrical properties were measured by LCR meter. The result obtained indicated the significant role of calcining temperature on phase transformation of boehmite and quartz into aluminosilicate geopolymer, in which at calcining temperatures from 450 oC to 550 oC, and  the samples were dominated by semicrystal to amorphous phase which indicated that the aluminosilicate geoplymer has been formed. The presence of aluminosilicate geopolymer resulted in increased ionic electrical conductivity and dielectric loss factor as well as decrease dielectric constant. Ionic electrical conductivity of the calcined sample at 450 oC is 4,49.10-5 S/cm at frequancy of 5.106 Hz, and XRD analysis demostrated that the main structure is phase of semicrystal aluminosilicate geopolymer. Based on these character, the sample was considered is very suitable used to the fast ionic conductor materials.Studi ini bertujuan untuk menginvestigasi efek suhu kalsinasi pada formasi fasa dan sifat listrik aluminosilikat geopolimer yang dipreparasi dari silika sekam padi dan sodium aluminat. Sampel dikalsinasi pada suhu 150 oC – 550 oC, perubahan struktur dikarakterisasi menggunakan x-ray difraction (XRD) dan sifat listrik diukur menggunakan LCR meter. Hasil yang diperoleh mengindikasikan pengaruh yang signifikan suhu kalsinasi pada transformasi boehmite dan quartz menjadi aluminosilikat geopolimer, dimana pada suhu kalsinasi 450 oC – 550 oC didominasi oleh fasa semikristal hingga amorf yang mencirikan terbetuknya aluminosilikat geopolimer. Terbentuknya struktur aluminosilikat geopolimer diikuti dengan peningkatan konduktivitas listrik ionik, penurunan konstanta dielektrik, serta peningkatan faktor rugi dielektrik. Nilai konduktivitas listrik ionik sampel kalsinasi 450 oC ialah 4,49.10-5 S/cm pada frekuensi 5.106 Hz, dan analisis XRD menunjukkan struktur utamanya berupa fasa semikristal aluminosilikat geopolimer. Berdasarkan karakteristik tersebut, sampel yang ditinjau merupakan material dengan konduktivitas ionik yang tinggi sehingga sampel tersebut sangat potensial untuk dimanfaatkan sebagai fast ionic conductor.